Worker#x2019;s Distribution Model: A Remedy for Global Economic Crisis by the Continuation of Work during Pandemic (Global Journal of Medical Research, 2020)
Introduction: Since the WHO declared COVID-19 as a global pandemic, nearly 80% of the global population has come under stay-home orders, lockdowns, and quarantines, inflicting increasingly severe direct and indirect economic impacts. Transmission of SARS-CoV-2 can occur through direct, indirect, or close-contact. The duration of RT-PCR positivity ranges from 1-3 weeks or more in some cases. The number of COVID-19 infections may be attributable to the late identification of sources-of-infection and the ability of the host to shed the infection while asymptomatic. The COVID-19 pandemic is wreaking havoc on the global economy, unleashing the worst economic downturn since the great depression. Managing the human resource in such a situation, keeping most of the workforce in quarantine is challenging. The idea of the Worker#x2019;s Distribution Model (WDM) of management is innovated. There is a global economic crisis during this pandemic. This WDM is justifiable to sustain the economic crisis of the country and stands aside to raise the economy of a country or community.
Keywords: pandemic; COVID-19; quarantine; epidemic; economic-crisis; worker#x2019; s distribution model; transmission; human resource